Prefontaine [videorecording (DVD)] - James, Steve, 1955-; James, Steve, 1955-; Leto, Jared, 1971-; Ermey, Lee; O'Neill, Ed, 1946- (Buena Vista Home Entertainment : Distributed by Mill Creek Entertainment, 2012)
The film features the true-life story of legendary track star Steve Prefontaine, the exciting and sometimes controversial "James Dean of Track."